Evaluation of antioxidant and DNA nicking potential along with HPTLC fingerprint analysis of different parts of Pterospermum acerifolium (L.) Willd - Paramaguru, Rathinavelusamy; Mazumder, Papiya Mitra; Sasmal, Dinakar; Kumar, Dhananjay; Mukhopadhyay, Kunal (Free Radicals and Antioxidants)
Objective: The present study was designed to evaluate the in vitro antioxidant and DNA nicking potential of various extracts and fractions of Pterospermum acerifolium (L.) Willd (Family: Stericuliaceae). Research design and methods: Antioxidant properties of the extracts and fractions was assayed by DPPH scavenging activity, non-site-specific and site-specific OH radical scavenging activity mediated 2-deoxy- D-ribose degradation, total antioxidant activity and lipid peroxidation assay by using rat liver homoge- nate. DNA nicking assay was studied by PT257R/T plasmid. Estimation of total phenolic content and total flavonoid content was done. Further HPTLC fingerprint of active fractions was performed. Results: Ethyl acetate fractions of leaves, flowers and bark exhibited potent antioxidant property and DNA protective effect compare to all the other extracts and fractions. Total phenolic and flavonoid content determination was also showed ethyl acetate fractions were rich in phenolic and flavonoid contents. HPTLC fingerprint revealed the total number of peaks present in the active ethyl acetate fractions of leaves, flowers and bark. Conclusion: The present study indicated that, ethyl acetate fractions of leaves, flowers and bark showed effective antioxidant and DNA protection activity and it could be the initiation for various other phar- macological studies on those fractions.
Keywords: PT257R/T plasmid; LPO assay; OH radical scavenging activity